Metodologi Penafsiran Kontekstual; Analisis Gagasan dan Prinsip Kunci Penafsiran Kontekstual Abdullah Saeed - Ridwan, M.K. (Institut Agama Islam Negeri (IAIN) Salatiga, 2016)
Qurâanic exegesis occupies a central position in the development of the intellectualÂ traditions of Muslims. As a primary source, the Qurâan for centuries have beenexplored and understood using a variety of approaches and methods to satisfy everyÂ need of the times. The dominance model of textual interpretation in the traditionÂ of interpretation of the Qurâan throughout the history of Islam, has been movingÂ Abdullah Saeed a Professor of Islamic Studies University of Melbourne, to offer anÂ alternative model of âcontextual interpretationâ as a model approach in interpretingÂ the Qurâan that more sensitive to context. Because textual interpretation modelsÂ tend to ignore the socio-historical context period of revelation as well as the contextÂ of the interpretation of the period. This paper specifically focused to analyzeÂ methodological aspects of thoughtâs Abdullah Saeed in conducting the contextualizeÂ interpretation of the Qurâan. In General, Saeed offers four contextual interpretationÂ of operational steps, that is: 1) identify initial considerations by understanding theÂ interpreter subjectivity, language and construct meaning, and the world of the QurâanÂ (encounter with the world of the text); 2) start the task of interpretation by meansÂ of identifying the meaning of the original text and convinced of the authenticityÂ and reliability of the text (critical analysis of texts independently); 3) identify theÂ meaning of the text by exploring each context (meaning for the first recipient); 4)Â hooking the interpretation of the text with the current context (process ofcontextualize, meaning for the present).